On the acquisition of European Portuguese liquid consonants by L1- Mandarin learners - Zhou, Chao (2022)
The present study aimed to investigate the developmental patterns of acquisition of the European Portuguese liquid consonants by L1-Mandarin speakers, and to examine the prosodic effect on L2 phonological acquisition. Fourteen L1-Mandarin learners participated in a picture-naming task and results showed that the alveolar lateral was produced accurately in branching/non-branching onset, while it was frequently vocalized in coda; the palatal lateral was produced as a Mandarin palatalised lateral nearly half of the time; the tap was acquired in coda before onset and the repair strategies were context-dependent: in non-target-like realisations, it was articulated as an alveolar lateral in onset but accommodated in diverse ways in coda (epenthesis, deletion, segmental repair); the uvular rhotic was acquired fairly well, however, its phonetic parameters were not mastered simultaneously by learners. Our results suggest that the degrees of difficulty in L2 segmental learning vary as a function of the relationship between L1 and L2 categories and the syllable constituency effect observed in the acquisition of the Portuguese alveolar lateral and the tap could be attributed to L2-to-L1 allophonic category mapping and L1 phonotactic restriction, respectively.